Quality of life in patients who underwent (125)I brachytherapy, (125)I brachytherapy combined with three-dimensional conformal radiation therapy, or intensity-modulated radiation therapy, for prostate cancer - Nakai, Yasushi (J Radiat Res, 2019)
The purpose of this study was to evaluate quality of life (QOL) in prostate cancer patients treated with (125)I brachytherapy (BT), (125)I brachytherapy combined with 3D conformal radiation therapy (BT+3D-CRT), or intensity-modulated radiation therapy (IMRT). We evaluated disease-related QOL in patients who underwent BT, BT+3D-CRT, or IMRT, using the Expanded Prostate Cancer Index Composite questionnaire before treatment and at 3 and 24 months post-treatment. Multivariate analyses were conducted to determine factors associated with a minimum important difference (MID) in urinary, bowel, sexual, and hormone domain scores at 3 and 24 months post-treatment. Of 558 enrolled patients (IMRT, 123; BT, 230; and BT+3D-CRT, 205), urinary domain scores showed a MID after BT, BT+3D-CRT and IMRT at 3 months in 69%, 84% and 25% of patients, respectively, and at 24 months in 43%, 54% and 28% of patients, respectively. On multivariate analysis, BT+3D-CRT [3 months: odds ratio (OR) = 12.7; P < 0.001; 24 months: OR = 3.29; P = 0.001] and BT (3 months: OR = 6.28; P < 0.001 and 24 months: OR = 2.22; P = 0.027) were associated with more severely worsened urinary QOL than IMRT. Bowel domain scores showed a MID at 3 months after BT, BT+3D-CRT, and IMRT in 37%, 68% and 41% of patients, respectively, and at 24 months in 29%, 46% and 43% of patients, respectively. On multivariate analysis, BT+3D-CRT (3 months: OR = 4.20; P < 0.001 and 24 months: OR = 2.63; P < 0.001) and IMRT (24 months: OR = 1.98; P = 0.029) were associated with more severely worsened bowel QOL than was BT. Information about the changes in QOL outcomes associated with radiotherapy modalities could guide treatment decisions.